2019
DOI: 10.1111/ans.15163
|View full text |Cite
|
Sign up to set email alerts
|

Primary duct closure combined with transcystic drainage versus T‐tube drainage after laparoscopic choledochotomy

Abstract: Background We compared the post‐operative course and final outcome of primary duct closure combined with transcystic drainage with those of T‐tube drainage. Methods We retrospectively analysed 112 consecutive patients treated with laparoscopic choledochotomy for common bile duct stones between February 2014 and December 2017. Primary closure with transcystic drainage was performed in 59 patients (group A), and laparoscopic choledochotomy with T‐tube drainage was performed in 53 (group B). The primary endpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although many studies have reported that transcystic approaches have shorter postoperative hospital stays and fewer bile leaks than choledochotomies[ 69 - 72 ], in most of the cases in our review, the latter was used. Senthilnathan et al [ 17 ] mentioned that a residual gallbladder containing small calculi was found six months after LC in an SI patient[ 17 ].…”
Section: Laparoscopic Common Bile Duct Exploration In Situs Inversus ...mentioning
confidence: 99%
“…Although many studies have reported that transcystic approaches have shorter postoperative hospital stays and fewer bile leaks than choledochotomies[ 69 - 72 ], in most of the cases in our review, the latter was used. Senthilnathan et al [ 17 ] mentioned that a residual gallbladder containing small calculi was found six months after LC in an SI patient[ 17 ].…”
Section: Laparoscopic Common Bile Duct Exploration In Situs Inversus ...mentioning
confidence: 99%